Маркетингове дослідження патології щитоподібної залози серед окремого контингенту медичних працівників обласніх лікувальних закладів міста Суми - Подорога, О. І.; Сьома, Л. І.; Бірюкова, О. В.; Миронцева, Л. М.; Хом'як, Н. А.; Радченко, Н. О. (Clinical Endocrinology and Endocrine Surgery, 2008)
The marketing study for thyroid pathology was performed among 1656 regional medical institutions workers aged from 17 to 70 years. There were 1468 women (88.6%) and 188 men (11.4%). Examined persons in ablebodied age were 1445 (87.3%) including 167 men (11.6%) and 1278 women (88.4%). All examined persons had sonography of thyroid gland, TSH estimation, peroxidase antibodies detection, fine needle aspiration by indication. In the structure of detected thyroid pathology nodular goiter has 32.5% that twice exceeds data of official statistics in Sumy region.